The Radicalization of Religion Understanding in Online Media and Its Effect on Student’s Religion Attitudes in Lampung Province - Mustofa, Imam (International Journal of Psychosocial Rehabilitation, 2020)
The development of science and technology has a major influence on the dynamics of changes in terrorism attacks. One of them is as a propaganda tool. As a developing country, the number of internet users in Indonesia is about 132.7 million populations. And this provides an opportunity for terrorist groups to carry out propaganda as a means of recruiting new followers. The radical extremists always try to find cadres and followers to carry out and continue their mission. One of the ways is through the radicalization of religion understanding by using internet media. The large number of internet users among students can be an entry point for them to spread their propaganda and recruit among them. Therefore, this study aims to uncover the radicalization of religious understanding in online media and its influence on students’ religious attitudes in Metro City. And it is the result of a qualitative-descriptive field research. This study found that the radicalization of understanding in online media is still happening and students as one of the most active users of the internet often read the provocative religious study content. These content incite and spread hatred to other people or groups. If the reader does not have a critical attitude and does not want to clarify and validate the source, it can provoke them to carry out destructive acts. Moreover, the proactive content is flavoured with religious texts. The study also found that the radicalization content in online media had no effect on the attitude and tolerance of students in Metro City. It does not affect their attitude towards other groups who differed in their religious understanding or people of other religions. They expressly state that they still have respect for those in other religions